Effects Of Firm Characteristics On Esg Disclosure In China: The Moderating Role Of Institutional Environment - Zhang, Yixi (2024)
Environment, social responsibility, and corporate governance (ESG) initiatives are considered as important business practices that assist the companies to achieve sustainable development for the business and the society. ESG activities have grown in popularity, and more companies are disclosing their ESG activities to indicate their engagement in social responsibility and to attract more investors. In China, over 40 years of economic reform have transformed the country into the biggest developing country in the world. However, although the number of listed companies in China has increased dramatically in the last decade, information transparency about their ESG activities has been lacking. The disclosure rate of independent ESG reports has remained around 25%, far lower than that of the developed Western countries. However, ESG disclosure in China is largely voluntary on the part of enterprises, and the factors influencing the motivation of corporate ESG disclosure are unclear.